THE RATIO "PRICE / EARNINGS" OF ACQUIRING AND HAS BEEN ACQUIRED COMPANIES ARE CONDITION AND ANALYSIS OF RELATIONSHIPS - O. Zemlyanskiy (Вестник университета)
There offer the method of calculation and formula of the ratio P/E-ratio «price/earnings» of acquiring and has been acquired companies relationships. This formula allow determining the required rate of growth forecasted profit after period one year.